1989
DOI: 10.1111/j.1365-2494.1989.tb01937.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dry feed additives on the nutritive value of silage

Abstract: Silages were prepared in late September from a mixed crop of perennial ryegrass and white clover with low dry matter and high nitrogen content. Six different treatments were used during ensiling; addition of either molassed sugar beet pulp or rolled barley, at 50 kg and 25 kg (t fresh grass)"', fonnic acid at 5 11~' and no additive (control).All silages were well fermented with low levels of ammonia and pH. The addition of rolled barley or sugar beet pulp increased the dry matter content ofthe silages incremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
3
7
1
Order By: Relevance
“…The inclusion of beet pulp with herbage at ensiling resulted in a significant increase in the apparent digestibilities of DM, OM, energy and fibre components in the silage, which although in contrast with the findings of Ferris and Mayne (1994a) is in agreement with the results of Moseley and Ramanathan (1989). The lack of consistency in these effects reflects difTerences in the digestibility of herbage ensiled between experiments and differences in the nutritive value of sugar-beet pulp.…”
Section: Apparent Digestibility Degradability and Food Utilizationsupporting
confidence: 62%
“…The inclusion of beet pulp with herbage at ensiling resulted in a significant increase in the apparent digestibilities of DM, OM, energy and fibre components in the silage, which although in contrast with the findings of Ferris and Mayne (1994a) is in agreement with the results of Moseley and Ramanathan (1989). The lack of consistency in these effects reflects difTerences in the digestibility of herbage ensiled between experiments and differences in the nutritive value of sugar-beet pulp.…”
Section: Apparent Digestibility Degradability and Food Utilizationsupporting
confidence: 62%
“…With the exception of the nitrogen component, silage digestibility, as determined using sheep, was relatively unaffected by beet pulp inclusion. This conflicts with the work of Moseley and Ramanathan (1989), who found the digestibility of the nitrogen component to be relatively unaffected by beet pulp inclusion. It is suggested that the lower digestibility of the nitrogen fraction of the beet pulp-treated silages in the present study is a reflection of the low digestibility of the nitrogen component of beet pulp relative to that of herbage harvested after a 50-day regrowth interval.…”
Section: Apparent Digestibility and Food Utilizationcontrasting
confidence: 83%
“…It is suggested that the lower digestibility of the nitrogen fraction of the beet pulp-treated silages in the present study is a reflection of the low digestibility of the nitrogen component of beet pulp relative to that of herbage harvested after a 50-day regrowth interval. In addition, silage ME concentrations were unaffected by treatment, again in contrast to the findings of Moseley and Ramanathan (1989). A comparison of diets offered in treatments S80, SM and ST, as determined using dairy cows, indicates that method of beet pulp inclusion had little effect on overall ration digestibility.…”
Section: Apparent Digestibility and Food Utilizationmentioning
confidence: 68%
“…Butler et al 47 described the non‐glycosidic cyanide as HCN gas which is entrapped by reaction with metal ions and/or carbonyl groups of hexoses to form cyanohydrins. The differences in the rate at which cyanide concentration decreased between the two mixture ratios at the onset of fermentation may be due to an increase in DM at ensiling which tends to improve fermentation, an observation confirmed by Moseley and Ramanathan 48…”
Section: Discussionmentioning
confidence: 70%